Краткий словарь по философии - Азаров Н. И.; Айзикович А. С.; Аникеев Н. П.; Анцыферова Л. И.; Арзаканьянц Ц. Г.; Астафьев А. К.; Афанасьев В. Г. (Москва, Политиздат, 1979)
Авторы указаны в конце книги.